Geographical imaginations - Gregory, Derek, 1951- (Cambridge, MA : Blackwell, 1994)
This work provides a reading of geography as a discipline and a discourse, and attempts to situate that discourse within the fabric of contemporary social theory. Its focus is on understanding the ways in which social life is variously embedded in place, space and landscape.
Maps of the intellectual landscape. Travelling theory -- 1. Geography and the world-as-exhibition. Visualization. Cook's Tour: anthropology and geography. Borders: sociology and geography. Frontiers: economics and geography -- 2. Geography and the cartographic anxiety. Descartes and deconstruction. Marks: political economy and human geography. Signs: social theory and human geography. Traces: cultural studies and human geography. Imaginative geographies and geographical imaginations -- 3. City/commodity/culture: spatiality and the politics of representation. Maps of modernity. The literary diver: David Harvey and Second Empire Paris. Passages: Walter Benjamin and the Arcades Project. The Vega cap: Allan Pred and fin-de-siecle Stockholm. Archives and archaeologies -- 4. Chinatown, Part Three? Uncovering postmodern geographies. Pastiche. A history of the present. Learning from Los Angeles. Watching the detectives. American dream. Dreams of unity -- 5. Dream of Liberty? Cover version. Imagining liberty. Representing power. Dream of Liberty. The condition of postmodernity -- 6. Modernity and the production of space. May 68 and Harvey 69. Hegel's ghost. A history of space. The eye of power. Dreams of liberty and wings of desire.
Includes bibliographical references (pages [417]-424) and index.
Keywords: Geography -- Philosophy